2013
DOI: 10.1186/1471-244x-13-276
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Hermansky–Pudlak syndrome type 4 (HPS4) gene variants with cognitive function in patients with schizophrenia and healthy subjects

Abstract: BackgroundThe Hermansky–Pudlak Syndrome Type 4 (HPS4) gene, which encodes a subunit protein of the biogenesis of lysosome-related organelles complex (BLOC)-3, which is involved in late endosomal trafficking, is associated with schizophrenia; however, its clinical relevance in schizophrenia remains unknown. The purpose of the present study was to investigate whether HPS4 is associated with cognitive functions in patients with schizophrenia and healthy controls and with the clinical profiles of patients with sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Of note, the HPS4 missense variant p.His154Arg (c.461A>G) was found homozygous in two Japanese siblings with HPS and mental disorder (schizophrenia and major depression). It was suggested that HPS4 gene single nucleotide polymorphisms variants may be associated with susceptibility to schizophrenia (A. Saito et al, 2013) and/or cognitive function (Kuratomi et al, 2013). However, there are no reports of other HPS‐related BLOC‐3 (HPS1 and HPS4) variants in individuals with HPS to be associated with neurological phenotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the HPS4 missense variant p.His154Arg (c.461A>G) was found homozygous in two Japanese siblings with HPS and mental disorder (schizophrenia and major depression). It was suggested that HPS4 gene single nucleotide polymorphisms variants may be associated with susceptibility to schizophrenia (A. Saito et al, 2013) and/or cognitive function (Kuratomi et al, 2013). However, there are no reports of other HPS‐related BLOC‐3 (HPS1 and HPS4) variants in individuals with HPS to be associated with neurological phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…This variant was found homozygous in two Japanese siblings with HPS and mental disorder (schizophrenia and major depression). It was suggested that HPS4 gene variants are associated with susceptibility to schizophrenia (A. Saito et al, 2013) and/or cognitive function (Kuratomi et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…The control subjects were volunteers from among mainly nonprofessional university/hospital staff, unrelated to the patients, and were free of any mental disorders. All subjects lived in the Kanto region of Japan, and some of them had been included in our previous studies (Akiyama et al, 2016; Kuratomi et al, 2013; Saito et al, 2013; Saito et al, 2017). Exclusion criteria included a history of neurological disorder, significant head injury, or substance dependence or abuse with the exception of nicotine.…”
Section: Methodsmentioning
confidence: 99%
“…The sex ratio between patients and healthy controls was analyzed using a chi-squared test. Age, JART-estimated premorbid IQ, education duration, and BACS z-scores were regarded as continuous variables and were assessed for a normal distribution using a Shapiro–Wilk test, and if appropriate, standardized and normalized across all of the subjects with a mean of zero and SD of one using rank transformation, as described previously (Kuratomi et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation